Climate refugia for Atlantic Forest widespread endemic anurans will persist in future climate change scenarios - Brasil-Godinho, Marcela; Diele-Viegas, Luisa; Bolochio, Bruna E. [UNESP]; Nogueira, Cristiano de C.; Sawaya, Ricardo J. (My University, 2024)
Anthropic influence has accelerated climate change rates and become a major cause of the sixth mass extinction. Conservation strategies such as identifying climate refugia can provide preliminary information for conservation planning. Our study aimed to identify climate refugia for 132 widespread endemic anuran species of the South America Atlantic Forest and assess their persistence in future climate change scenarios. Using species distribution models, we generated geographic projections for six time periods, including the Last Interglacial, Last Glacial Maximum, Mid Holocene, current time, and two periods in the future under two climate change scenarios each. We defined climate refugia as areas where the geographic distributions of species overlapped in the three time periods in the past and present. We observed a maximum overlap of 40 species and found them mainly in parts of the southeastern and northeastern Atlantic Forest. These refugia should remain suitable for most species in future climate change scenarios, making them important for conservation. Our study highlights the importance of these areas to maintain biodiversity and prevent the loss of endemic anuran species in the megadiverse Atlantic Forest. Overall, our findings have important implications for conservation planning in the Atlantic Forest and other regions affected by climate change.
Keywords: Amphibia; Atlantic Forest; Biological conservation; Climate refugia; Species distribution models